1972
DOI: 10.1111/j.1432-1033.1972.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Rate-Limiting Step in Microsomal Hydroxylation of Steroids

Abstract: The rate-limiting step in the microsomal, NADPH-dependent 24-and 26-hydroxylations of 5@-cholestane-3a,7aI,12a-triol, 60-hydroxylation of testosterone and 16n-hydroxylation of pregnenolone has been studied. Possible isotope effects were determined when the hydrogen in the substrate which is removed in the hydroxylation was substituted with deuterium; when the 4A-or 4B-hydrogen in NADPH was substituted with deuterium ; and when the incubation was carried out in deuterated water. 3. When the reactions were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The kinetic isotope effect on T V/K was 2.3-fold. It was previously reported that 6␤-hydroxylation of deuterated testosterone proceeds in the absence of a kinetic isotope effect (Bjorkhem, 1972). This is most likely due to the difference between C-D and C-T bond energies.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic isotope effect on T V/K was 2.3-fold. It was previously reported that 6␤-hydroxylation of deuterated testosterone proceeds in the absence of a kinetic isotope effect (Bjorkhem, 1972). This is most likely due to the difference between C-D and C-T bond energies.…”
Section: Discussionmentioning
confidence: 99%
“…KIE measurements have been made in many systems, but what new information has resulted? Many of the earliest studies were of the intermolecular competition type, and several investigators concluded that KIEs were absent or modest (Björkhem, 1972; M. Tanabe et al, 1967; Ullrich, 1969).…”
Section: Examples Of P450 Kie Studiesmentioning
confidence: 99%
“…The nature of P450 chemical reactions led to early forays into the use of KIEs as a mechanistic tool . However, many of the early studies were difficult to interpret in that (i) the studies contained mixtures of P450s and (ii) a variety of experimental designs were used . However, a high (intrinsic) D k was one of the points Groves et al .…”
Section: History Of P450 Kinetic Isotope Effectsmentioning
confidence: 99%